Comparative study of the physical and tensile properties of Jicama (Pachyrhizus erosus) starch film prepared using three different methods - Abral, Hairul; Riyan, Soni Satria; Mahardika, Melbi; Hafizulhaq, Fadli; Affi, Jon; Asrofi, Mochamad; Handayani, Dian; Salit, Mohd Sapuan; Stephane, Ilfa; Sugiarti, Eni; Muslimin, Ahmad Novi (WILEY-VCH Verlag, 2019)
The objective of this work is to study the physical and tensile properties of jicama (Pachyrhizus erosus) starch film prepared using three different methods. First, a film is prepared from starch granules after sifting using a sieve shaker. A second film is prepared from starch granules after ultra-sonication. Another film is made by sonicating the starch gel. Ultrasonication is performed using an ultrasonic probe. These three different methods have a significant effect on the properties of the film (p  0.05). The film from the starch granules after sifting using 63μm mesh size and ultrasonication (labeled as S-63U film) shows the optimum properties. Opacity for S-63U film is almost half (48.6%) that of the equivalent non-sonicated film. S-63U film has the highest tensile strength (3.1 MPa), the lowest moisture absorption (18% after 8 h in a humid chamber) and water vapor permeability. FESEM morphology of the fracture surface of the sonicated film display a more homogeneous structure compared to films without ultrasonication